2020
DOI: 10.1002/adfm.202010174
|View full text |Cite
|
Sign up to set email alerts
|

The Interlayer Method: A Universal Tool for Energy Level Alignment Tuning at Inorganic/Organic Semiconductor Heterojunctions

Abstract: The combination of inorganic and organic semiconductors in a heterojunction is considered a promising approach to overcome limitations of each individual material class. However, to date only few examples of improved (opto‐)electronic functionality have been realized with such hybrid heterojunctions. The key to unraveling the full potential offered by inorganic/organic semiconductor heterojunctions is the ability to deliberately control the interfacial electronic energy levels. Here, a universal approach to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…Different electrical properties could provide higher or lower charge carrier density flowing throughout the device as, e.g, charge carrier mobility from the semiconductor or energy alignment at the interfaces. This second example can be improved by playing with the energy level matching at the interface of two different materials that can be semiconductor/semiconductor (S/S) or metal/semiconductor (M/S) interfaces [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different electrical properties could provide higher or lower charge carrier density flowing throughout the device as, e.g, charge carrier mobility from the semiconductor or energy alignment at the interfaces. This second example can be improved by playing with the energy level matching at the interface of two different materials that can be semiconductor/semiconductor (S/S) or metal/semiconductor (M/S) interfaces [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The addition of an interlayer between M/S interfaces is a common technique to improve charge carriers injection 8,9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of active materials that have an excellent photoelectric effect is a very significant topic. Currently, our research on photoelectric materials is mainly focused on the inorganic semiconductor materials, , which are often limited in application due to inefficient light absorption, and so forth. Organic semiconductors have gradually become a research point of special interest and have increasingly fascinated researchers due to their fast light response, low cost, easy processing, and so forth. , In addition, organic materials possess diverse structural compositions and properties, which allow us to design their molecular structure for achieving the desired performance and significantly promote their wide application in the photoelectric field. Porphyrins are an important class of molecular semiconductors that have been designed into a variety of functional materials for photoelectric conversion, conductive sensing, photolysis of water, , and catalysis , owing to their unique electronic structure and optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of active materials that have an excellent photoelectric effect is a very significant topic. Currently, our research on photoelectric materials is mainly focused on the inorganic semiconductor materials, 7,8 which are often limited in application due to inefficient light absorption, and so forth. Organic semiconductors have gradually become a research point of special interest and have increasingly fascinated researchers due to their fast light response, low cost, easy processing, and so forth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A promising approach to meet this requirement is the use of strong molecular acceptors such as the recently synthesized 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane (F 4 TCNQ) and 1,3,4,5,7,8-hexafluorotetra-cyanonaphthoquinodimethane (F 6 TCNNQ), that are often used as p-dopants in OSC films, also for the preparation of contact primer layers. [18] Previous studies have shown, that for such adlayers adsorbed on metal surfaces the push-back effect is compensated by a notable charge transfer…”
mentioning
confidence: 99%